Room-temperature air-stable spin transport in bathocuproine-based spin valves - Sun, Xiangnan (2013)
Organic semiconductors, characterized by weak spin-scattering mechanisms, are attractive materials for those spintronic applications in which the spin information needs to be retained for long times. Prototypical spin-valve devices employing organic interlayers sandwiched between ferromagnetic materials possess a figure of merit (magnetoresistance (MR)) comparable to their fully inorganic counterparts. However, these results are a matter of debate as the conductivity of the devices does not show the expected temperature dependence. Here we show spin valves with an interlayer of bathocuproine in which the transport takes place unambiguously through the organic layer and where the electron spin coherence is maintained over large distances (>60 nm) at room temperature. Additionally, the devices show excellent air stability, with MR values almost unaltered after 70 days of storage under ambient conditions, making bathocuproine an interesting material for future spintronic applications.